The 2014 Referendum in the Scottish Press. Issue 1 (February 2018) - Dekavalla, Marina
Abstract : This essay discusses how Scottish newspapers covered the 2014 Scottish independence referendum. It suggests that, in a move away from the positions they had held in the previous decade, indigenous Scottish newspapers openly suggested there was a desire for change in the form of increased devolution. As this option was not on the ballot paper, most of them proposed that increased devolution could still be achieved inside the Union. The mediated debate in the press was not about traditional notions of national identity, but about pragmatic considerations affecting everyday life, such as the future of the economy and public services. Although most of the press in its majority did not support independence, it did not wholeheartedly endorse the status quo either.